ACAPELLA-1K, A Capillary-Based Submicroliter Automated Fluid Handling System for Genome Analysis - Meldrum, Deirdre R.; Evensen, Harold T.; Pence, William H.; Moody, Stephen E.; Cunningham, David L.; Wiktor, Peter J.

(untitled) (Genome Research, 2000)
The Genomation Laboratory in the Electrical Engineering Department at the University of Washington has been developing an automated, high-throughput, submicroliter-scale fluid-handling system for use in molecular biology, especially as part of the Human Genome Project and other high-throughput DNA sequencing endeavors. Small glass capillaries enable the preparation, handling, and monitoring of 1-μl reaction volumes. The Genomation Laboratory, with corporate partners Orca Photonic Systems, Inc. and Engineering Arts, has developed modules for aspiration, dispensing, mixing, transport, and rapid thermal processing of biological samples contained in glass capillaries. The ACAPELLA-1K is the first integration of these modules, designed to process 1000 samples in an eight-hour day. It has served as a test bed for the technologies as well as for performing biological experiments in conjunction with the University of Washington Genome Center. This system and related results are presented in this paper. A video of the system in operation is provided at http://www.genome.org. The Genomation Laboratory is presently developing the next-stage ACAPELLA-5K system based on the results of the ACAPELLA-1K system.